Aktywność gospodarcza Jana i Kazimierza Arkuszewskich jako przedstawicieli kapitału polskiego na terenie Łodzi i Królestwa Polskiego do roku 1914 - Klemantowicz, Dariusz (Acta Universitatis Lodziensis. Folia Historica, 1998)
Favourable conditions for development of industry in Łódź during the second half of the XIXth century and at the beginning of the ХХШ century were not used profitably by Polish bourgeois which was created then. Polish enterprise met a strong competition from more active and professional Germans and Jews, who operated a large amount of capital. Cousins Jan and Kazimierz Arkuszewski were among few Polish entrepreneurs who achieved a real success. They were well educated (they both graduated from the Institute of Technology in Petersburg) and family capital enabled them to start their business activity - at first placed only in Łódź. After several years they were among middle class entrepreneurs, but also among the richest Polish manufacturers of Łódź. K. Arkuszewski who became a co-owner of the Mechanical Plant „E. Plage and T. Laśkiewicz” entered even the upper class business (employed 201-500 workers). Machines produced by Arkuszewskis’ factory became well known for their quality and the plant won great popularity in the Kingdom of Poland. It was first Łódź plant which Produced central heating equipment and among first such plants in Poland. Arkuszewskis were involved not only in metal and machine industry, but also in other branches, for example in food industry.